A festa de iemanjá no mercadão de Madureira: uma análise histórica dos conflitos políticos e religiosos durante a gestão de Marcelo Crivella 2017-2020 - FIRMINO, Jonatan da Silva Alves (2024)
This study proposes a historical investigation into the political-religious conflicts involving the Iemanjá Festival at Mercadão de Madureira during the administration of former mayor Marcelo Crivella in the city of Rio de Janeiro. The celebration is interpreted as a manifestation of cultural and religious resistance, in addition to being perceived as a form of occupation of public space. During Crivella's administration, the festival faced considerable challenges, reflecting complex political-religious interactions. Although it had institutional support, it was also subject to restrictions, especially in 2019, due to resource limitations that prevented it from being carried out in traditional ways. This situation represents the clash between Afro-Brazilian traditions and municipal policies, influencing the visibility and continuity of the party. The study concludes that the Iemanjá Festival at Mercadão de Madureira is emblematic of the interaction between religion, culture, politics and the suburban territory of Rio de Janeiro. From a theoretical and methodological point of view, this research is based on the concepts of Cultural History, as outlined by Peter Burke, and on the concepts of Oral History, as understood by Paul Thompson. Focusing on the intersection between Afro-Brazilian culture and the political panorama in the city during the period from 2017 to 2020, the work uses semi-structured interviews to investigate how the party, started in 2003 and organized by Mercadão traders, reflects the identity and the social dynamics of Rio's suburban regions, as well as its relationship with Crivella's administration in this period. In addition to interviews, the sources used in this research include newspapers, legislation and municipal decrees, and social media platforms.